The Effectiveness of Targeted Electrical Stimulation via Cochlear Implant on Tinnitus-Perceived Loudness - Di Nardo, Walter; Di Cesare, Tiziana; Tizio, Angelo; Paludetti, Gaetano; Fetoni, Anna Rita (Frontiers in Neuroscience, 2022)
Introduction The cause of tinnitus improvement in cochlear implant (CI) users is not understood. On the basis that a spatially limited dysfunction in the auditory pathway could cause tinnitus, we used single-channel stimulation to evaluate any variation of tinnitus-perceived loudness and identify the cochlear regions involved. Materials and Methods It was an observational prospective case-crossover study. After the first mapping, 21 adults with unilateral CI and chronic tinnitus expressed their tinnitus loudness based on the Visual Analog Scale (VAS) score (0–10) at baseline (L0), during a 10 s single-channel stimulation with C-level of electric current (L1) and 30 min after CI activation (L2). Tinnitus reduction [RT = (L0 – L1) × 100/L0] > 50% was considered significant. VAS outcomes were compared between baseline (L0) and (each) single-channel stimulation (L1) to find the channel with the greatest RT (suppressive channel-SC), whose frequency range revealed the cochlear region involved. Seven patients with asymmetric hearing loss underwent the pitch-matching test to identify the actual frequency evoked by the SC. We compared selective (L1) and non-selective (L2) intracochlear stimulation using paired t-test. Preoperative Tinnitus Handicap Inventory (THI) score was compared with those at 1, 6, and 12 months with paired t-tests to evaluate long-term tinnitus perception. Results We observed a significant reduction of tinnitus loudness during the experimental procedure [L0 (6.4 ± 2.4) vs. L1 (1.7 ± 2.7), p = 0.003]. A total of 15/21 patients (71.4%) had a significant (RT > 50%) and selective improvement, reporting a mean L1 of 0.4 ± 2.0 (p = 0.0001). In 10/15 (66.6%) patients, the SC was in the apical turn, within 1,000 Hz; in 5/15 patients (33.4%) within 4,000 Hz. The cochlear region 125–313 Hz was the most affected by tinnitus improvement (p = 0.0074). Targeted stimulation was more effective than non-selective stimulation [L1 vs. L2 (4.3 ± 2.5), p = 0.0022]. In 3/7 patients, the perceived pitch did not fall within the SC frequency ranges. All patients with selective attenuation described tinnitus as monotone. Patients with non-selective attenuation had polyphonic tinnitus and better THI results after 1 year. Conclusion Targeted intracochlear electrical stimulation improved chronic tinnitus perception, especially in monotone tinnitus, and the apical region was mainly involved. Our results provide new insights into the pathophysiological mechanisms of tinnitus and targets for innovative therapeutic strategies.